The Effects of Recreative Activities on Adjustment Levels of Young People - Sivrikaya, Kenan (Asian Journal of Education and Training, 2019)
This study was planned to determine the effect of a series of 8-week recreational activities on the personal, social and general adjustment levels and academic success of high school students (between 14-16 years). The data was collected from a total of 36 students, made up two groups each containing 18 members. They were all recruited voluntarily from students in the first year class of the Mugla Mimar Sinan High School. The data collected were analyzed using the SPSS 21 software and complemented by the Mann Whitney U and Kruskal-Wallis variance analysis techniques. Significant differences (0.01) were found between the pre-test and post-test scores for anti-social inclinations in the experimental group. Significant differences (0.01) also were found between the post-test scores for anti-social inclinations in the experimental and the control groups. Significant differences (0.05) were found between the pre-test and post-test scores for emotional determinants in the experimental group and the pre-test and post-test scores for social adjustment in the experimental group. No significant difference was found between other parameters among the groups. It was concluded at the end of the study that recreation was effective on the adjustment level of the adolescents and that this effect was also noted to positively affect the academic success of the subjects.